Modelling several morphometric relationships of swordfish (Xiphias gladius), black marlin (Makaira indica) and blue marlin (Makaira nigricans) caught from Indonesian longliners in the eastern Indian Ocean - Setyadji, Bram; Jatmiko, Irwan; Wujdi, Arief (Journal of Fisheries, 2016)
This paper presents several equations for converting among measures of size (length and weight) for swordfish (Xiphias gladius), black marlin (Makaira indica) and blue marlin (Makaira nigricans) caught by Indonesian longliners in the Indian Ocean. The equations use for transforming non-standard measurement i.e. eye fork length (EFL) and pectoral fork length (PFL) to standard measurement, lower jaw fork length (LJFL). The paper also discussed about the length-weight relationship, including converting from non-standard length (EFL and PFL) to round weight. The result showed that both PFL and EFL were positively related to LJFL but there were no significant differences existed between females and males among length measures for swordfish, blue marlin, and black marlin (ANCOVA, P>0.05). All regression equation models were considered to be valid (P<0.01) with coefficient of determinations (r2) ranged from 0.81-0.99. Allometric growth pattern was statistically observed for all swordfish (b=2.94, r2=0.94), black marlin (b=3.12; r2=0.90) and blue marlin (b=3.30; r2=0.91).